The role of colchicine therapy in the treatment of postpericardiotomy syndrome - Nóra Kalina; László Kohut; Marcell Székely; Éva Szökő (Cardiologia Hungarica, 2025)
Introduction: Postpericardiotomy syndrome is a common condition among pericardial diseases in clinical practice. The aim of our study was to survey the incidence and treatment options of postpericardiotomy syndrome during the early rehabilitation following open-heart surgery. Patients and methods: Our retrospective consecutive study is based on data from patients referred from one cardiac surgery center over a six-month period. 174 patients who had undergone open-heart surgery (mean age 64.49±10.86 years, 125 males) were included in our work, with an average rehabilitation stay of 20.07±4.32 days. The amount of pericardial fluid was measured using echocardiography. The postpericardiotomy syndrome was diagnosed according to the European Society of Cardiology’s definition and the CRP threshold of 50 mg/L observed during the study. Our data analysis included descriptive statistics, two-sample t-tests, chi-square tests, and simple logistic regression